The agnostic's response to climate deniers: price carbon! - Van der Ploeg, R; Rezai, A (University of Oxford, 2017)
With the election of President Trump, climate deniers moved from the fringes to the centre of global policy making and need to be addressed in policy-making. An agnostic approach to policy, based on Pascal's wager, gives a key role to subjective prior probability beliefs about whether climate deniers are right. Policy makers that assign a 10% chance of climate deniers being correct set the global price on carbon to $19.1 per ton of emitted CO2 in 2020. Given that a non-denialist scientist making use of the DICE integrated assessment model sets the price at $21.1/tCO2, agnostics' reflection of remaining scientific uncertainty leaves climate policy essentially unchanged. The robustness of an ambitious climate policy also follows from using the max-min or the min-max regret principle. Letting the coefficient of relative ambiguity aversion vary from zero corresponding to expected utility analysis to infinity corresponding to the max-min principle, it is possible to show how policy makers deal with fundamental climate model uncertainty when they are prepared to assign prior probabilities to different views of the world being correct. Allowing for a wide range of sensitivity exercises including damage uncertainty, it turns out that pricing carbon is the robust response under rising climate scepticism.